PERSEPSI SISWA TENTANG PELAKSANAAN MODEL PROBLEM BASED LEARNING BERBASIS MEDIA ONLINE DALAM PEMBELAJARAN IPAS KELAS IV SD NEGERI KAYUARES - Retnowati, Anggun; Muslim, Arifin (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to examine students’ perceptions and the factors influencing their perceptions of the implementation of the Problem-Based Learning (PBL) model supported by online media in Integrated Science and Social Studies (IPAS) learning in a fourth-grade elementary classroom. The research employed a descriptive qualitative method, with data collected through observation, interviews, and documentation. The subjects of the study were fourth-grade students at SD Negeri Kayuares, involving six students and one teacher in the 2024/2025 academic year. The findings indicated that students had positive perceptions of the implementation of online media-based PBL, as reflected in their enthusiasm during the learning process and improved understanding of the material. The model encouraged active engagement, enhanced conceptual understanding, and facilitated contextual and meaningful learning. The use of digital media, such as educational videos, Quizizz, and interactive applications like Assemblr Edu, also contributed to increasing students’ learning motivation. In conclusion, online media-based PBL is effective in supporting engaging and meaningful learning. This study recommends strengthening digital infrastructure support and providing teacher training to optimize the implementation of PBL in elementary education.